THE IMPORTANCE OF TEACHING ENGLISH IN TODAY’S MODERN LIFE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In today’s globalized world, English has become the dominant language in many sectors, including business, science, technology, and international relations. This paper explores the importance of teaching English as a second language, particularly in non-English speaking countries. It highlights the role of English in facilitating communication across cultures, expanding career opportunities, and promoting personal development. The study also emphasizes the growing necessity of English proficiency in the modern job market and its impact on the economy. Moreover, it discusses the methods and strategies for teaching English effectively in various educational contexts.